The Impact of Machine’s and Students’ Translation on Accuracy of Roda Kehidupan - Sipayung, Kammer Tuahman (Lingua Cultura, 2023)
The research aimed to describe the impact of machine translation on translation accuracy. Machine translation was widely used to translate the original language to the target. Accuracy was a crucial thing that the translator needed to restructure in the target language. The research applied a qualitative method with sampling based on its criteria. In addition, the research had two types of data: objective and effective. There were two instruments used to collect data; the first was instruction for translating a short film entitled “Roda Kehidupan”. The students were asked to translate a short film with the help of a machine, without machine translation, and the final version of the translation. The second instrument was the translation accuracy indicator, formulated in indicator form. The translation accuracy indicator (questionnaire) was distributed to inter-raters. The research shows that the accuracy of translation without machine translation (first version) is inaccurate (1,5); however, the accuracy of translation with machine translation (second version) is categorized as less accurate (2,4), and the translation accuracy on the final version of the translation is 2,3 (less accurate). The researcher suggests that the translator and lecturer need to use machine translation in translating, but a human touch (post-editing of translation) is really important to achieve high translation quality.